2014
DOI: 10.11118/actaun201462040783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Consumer Behavior of Slovaks and Czechs in the Market of Organic Products by Using Correspondence Analysis

Abstract: This article aims to collect information related to organic farming. It also deals with the assessment and comparison of shopping behaviour in the organic food market in the Czech and Slovak Republics. Respondents from the Czech Republic and the Slovak Republic were addressed within the marketing research -survey and potential factors that could aff ect young people when buying organic products were formulated. There were also established recommendations to retailers of organic products on how to promote the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…Not insignificant number of participants in our survey also consider organic food to be healthier and of superior quality, plus show interest in its place of origin. Zámková and Prokop (2014) proved that the number of Czech and Slovak respondents shopping for organic food regularly is only negligible. Our research have similarly demonstrated that there are very few young people who buy organic products regularly and these were also the ones, who most often claimed they do not buy organic food at all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not insignificant number of participants in our survey also consider organic food to be healthier and of superior quality, plus show interest in its place of origin. Zámková and Prokop (2014) proved that the number of Czech and Slovak respondents shopping for organic food regularly is only negligible. Our research have similarly demonstrated that there are very few young people who buy organic products regularly and these were also the ones, who most often claimed they do not buy organic food at all.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis focused on the Czech Republic. Similarly, Zámková and Prokop (2014) have assessed the consumer behaviour at the organic market in the Czech and Slovak Republic. The differences between the sales of organic food in Greece and in the Czech Republic were analysed by the pair of authors Zámková and Blašková (2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the following part, the hypotheses on the dependence of the gender and age of the respondents were tested, using the Pearson chi-quadrate test. To evaluate the results of the research, the correspondence analysis was used, too, as another suitable method of evaluating the categorical type of data, which makes it possible to compare the results from the contingency table (Zámková, Prokop, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It is conceptually similar to principal component analysis but applies to categorical rather than continuous data. In a similar manner to principal component analysis, it provides a means of displaying or summarizing a set of data in a two-dimensional graphical form (Zámková & Prokop, 2014). All data should be non-negative and on the same scale for CA to be applicable, and the method treats rows and columns equivalently.…”
Section: Methodsmentioning
confidence: 99%